The open-source software LRmix can be used to analyse SNP mixtures. (December 2015) - Gill, Peter; Haned, Hinda; Eduardoff, Mayra; Santos, Carla; Phillips, Chris; Parson, Walther
Abstract: A series of two- and three-person mixtures of varying ratios were prepared and analysed with Life Technologies' HID-Ion AmpliSeq™ Identity Panel v2.2 using the Ion PGM™ massively parallel sequencing system. This panel includes 136 autosomal SNPs and 33 Y-chromosome SNPs. Using the reference samples of the mixture donors, we evaluated the strength of evidence with likelihood ratio (LR) calculations using the open-source LRmix program. This program was designed for multi-allelic STRs, but can be extended to bi-allelic SNPs without modification. We conditioned on each donor in turn, as the person of interest (POI) in the numerator. The LR tests showed that two-person mixtures typically gave LRs of the order of >10 8 whereas three-person mixtures were highly variable in results. Approximately 50% of results were exclusionary or neutral. The remainder provided LRs ranging between 10 3 –10 8 . We further evaluated these mixtures using diagnostic non-contributor tests. Our preliminary work shows that simple two-person mixtures can be readily analysed with LRmix, but the performance of three- or more person mixtures is less predictable and may fail to provide probative evidence. However, if a higher number of loci were multiplexed, the analysis of mixtures would be improved, particularly if less frequent variation (allele frequencies below 0.1) was targeted in identity SNP selection.